1994
DOI: 10.1165/ajrcmb.10.4.8136152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracellular ATP and UTP on fluid transport by human nasal epithelial cells in culture.

Abstract: We have investigated the effect of both adenosine triphosphate (ATP) and uridine triphosphate (UTP) on the fluid transport, transepithelial electric potential difference (PD), and unidirectional chloride flux when applied apically to cultured human surface respiratory epithelial (HSRE) cells in a double-compartment chamber. The effects of ATP and UTP (both 100 microM) were examined in cells either untreated or pretreated with 100 microM amiloride in lactated Ringer's solution. ATP or UTP was added to the apica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Extracellular ATP increases fluid transport by human nasal epithelial cells in culture (Benali et al, 1994). Evidence was presented to suggest that ATP acts as a cotransmitter with NA in sympathetic nervous control of blood vessels of the nasal mucosa of cats and dogs (Lacroix et al, 1994).…”
Section: Nasal Mucosamentioning
confidence: 99%
“…Extracellular ATP increases fluid transport by human nasal epithelial cells in culture (Benali et al, 1994). Evidence was presented to suggest that ATP acts as a cotransmitter with NA in sympathetic nervous control of blood vessels of the nasal mucosa of cats and dogs (Lacroix et al, 1994).…”
Section: Nasal Mucosamentioning
confidence: 99%
“…The P2Y 2 receptor is abundant on the luminal surface of polarized epithelial cells, especially those lining mucosal surfaces exposed to the external environment. The pharmacology of the P2Y 2 receptor has been established, and the effects of P2Y 2 agonists on epithelial cell functions are numerous, including stimulation of serosal to mucosal chloride and fluid transport (Knowles et al, 1991;Benali et al, 1994;Tarran et al, 2000), enhancement of mucin secretion from goblet cells (Lethem et al, 1993;Kim et al, 1996), increase in cilia beat frequency (Morse et al, 2001), and promotion of surfactant release from type II alveolar cells (Gobran et al, 1994). Additionally, tracheal mucus velocity (TMV), a measure of mucociliary clearance in a single large airway, has revealed the mucokinetic effects of nucleotides and various other agents in the lung in vivo (Sabater et al, 1996).…”
mentioning
confidence: 99%
“…Recently, LETHEM et al. [4] demonstrated that uridine triphosphate (UTP) is almost equipotent with adenosine triphosphate (ATP) in its ability to stimulate mucin release from human airway epithelial explants [4], suggesting the presence of a receptor type specific both for ATP and UTP in airway epithelial cells, which may regulate the mucin release.The presence of this type of purinoceptor has been identified in a number of systems [6,7], including airway epithelial cells, which involve the regulation of ion transport [8,9], and have recently been classified as the …”
mentioning
confidence: 99%
“…The presence of this type of purinoceptor has been identified in a number of systems [6,7], including airway epithelial cells, which involve the regulation of ion transport [8,9], and have recently been classified as the…”
mentioning
confidence: 99%